Business incubation practices and sustainability of incubatee start-up firms in Uganda - Bob Ssekiziyivu; Yoram Banyenzak (Cogent Business & Management, 2021)
The purpose of this study was to establish the relationship between business incubation practices and sustainability of incubatee start-up firms in Uganda using business incubation theory and network theory. A quantitative methodology is used for data collection based on 110 incubatee start-up firms from 8 incubators in Uganda. It is a cross-sectional descriptive study, which investigates the causal effect of variables at a definite point in time. A principal factor analysis was conducted to single out the particular constructs of business incubation practices and sustainability. Simple random sampling was used for selecting start-ups from the incubation centres. The sampling framework consists of the founders of the start-ups that have been previously incubated at any of the selected incubation centres. Data were analysed using Statistical Package for Social Sciences. Incubatee selection criteria, incubatee monitoring practices and resources have a positive and significant impact on sustainability of incubatee start-up firms. The study has emphasised good business incubation practices to enable sustainability of start-up firms in Uganda. This study was limited to only incubators in Uganda and it is possible that the results are only applicable in Uganda. This paper adds to the limited business incubation literature and provides the first empirical evidence of business incubation practices on sustainability of incubatee start-up firms in Uganda.
Keywords: 650; business incubation; sustainability; incubatee start-up firms; Uganda